2010
DOI: 10.1128/jcm.00605-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Protease Inhibitor Drug-Resistant Mutants Give Discordant Results When Compared in Single-Cycle and Multiple-Cycle Fitness Assays

Abstract: The replication fitness of HIV-1 drug-resistant mutants has been measured using either multiple-cycle or single-cycle assays (MCAs or SCAs); these assays have not been systematically compared. We developed an MCA and an SCA that utilized either intact or env-deleted recombinant viral vectors, respectively, in which virus-infected cells were detected by flow cytometry of a reporter gene product. Fitness was measured using each assay for 11 protease mutants, 9 reverse transcriptase mutants, and two mutants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Although this replication capacity assay remains an interesting research tool, it has not found a definitive role in patient management (39). Multiple cycle replication assays tend to amplify small differences in viral replication (17,80), which are often indistinguishable in single-cycle infection, especially VOL. 55,2011 NOVEL HIV-1 PHENOTYPING ASSAY 3739 where virus infection is monitored only until HIV-1 mRNA transcription in trans (i.e., luciferase expression) and does not account for viral protein translation, assembly, and virion maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Although this replication capacity assay remains an interesting research tool, it has not found a definitive role in patient management (39). Multiple cycle replication assays tend to amplify small differences in viral replication (17,80), which are often indistinguishable in single-cycle infection, especially VOL. 55,2011 NOVEL HIV-1 PHENOTYPING ASSAY 3739 where virus infection is monitored only until HIV-1 mRNA transcription in trans (i.e., luciferase expression) and does not account for viral protein translation, assembly, and virion maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The assays used to test stimulation were multiple-cycle assays, which include all steps of the virus life cycle, both early steps (entry, reverse transcription, and integration) and late steps (RNA production, protein expression, and viral particle production). In order to determine whether stimulation occurred during early or late steps, we modified a single-cycle assay previously designed by our group (13). We used the envelope-deleted vector, pDAT2, and with a murine leukemia virus (MLV) envelope-expressing construct, made MLV-pseudotyped virus stocks in the presence or absence of EFV.…”
Section: Efv Increases the Number Of Cells Infected With The K101e؉ Gmentioning
confidence: 99%
“…The wild-type (WT) and mutant pAT2 and pNL4-3XX constructs were transiently transfected into either 293 cells using 40 g of plasmid DNA and Superfect (Qiagen) or 293T cells using 5 g of DNA and 25 l of Lipofectamine LTX (Invitrogen) in the absence of drug. Mutant pDAT2 constructs were transiently transfected into 293 or 293T cells using 5 g of plasmid DNA along with 5 g of pSV-A-MLV-ENV (expressing the murine leukemia virus [MLV] envelope [ENV]) and 25 l of Lipofectamine LTX (Invitrogen) as previously described (13). For all transfections, the cells were incubated for 4 h, and the transfection medium was replaced with fresh medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DHIV was obtained from Vicente Planelles (Bosque and Planelles, 2009). Plasmid expressing the vesicular stomatitis virus G protein (VSV-G) under the control of the human cytomegalovirus promoter (pHCMV-g) was obtained from Carrie Dykes (Dykes et al , 2010). Human embryonic kidney 293T cells were used for generation of HIV-1 stocks.…”
Section: Methodsmentioning
confidence: 99%